Microcomputer engineering - Miller, Gene H., ....- (New Jersey : Pearson Education, 2004)
This complete book and laboratory manual focuses on microcomputers and microprocessors used as control devices (e.g., the Motorola 68HC11). It includes extensive material on using the Motorola M6HC11EVB and M68HC11EBU Trainers and encourages hands-on learning. KEY TOPICS Specific chapter topics cover computer fundamentals, instruction subset and machine language, assemblers and assembly language, program structure and design, advanced assembly language programming, hardware, advanced 68HC11 hardware, real-time operating systems, and real-time system design. For individuals studying, for the first time, microcomputers/microcontrollers.
Includes index
Keywords: Electronic and Computer Engineering; Microcomputer-randapparaten.